(untitled) (Global Journal of Management and Business Research, 2015)
This study examines the level of customer satisfaction and service quality of e-reader devices has stores and SPSS22 software was used for data analysis and correlation tests to determine the relationship of variables, the analysis of the test for identification of direct and indirect effects of variables has been used on customer satisfaction. The population of this study, shoppers and stores are Ardakan, Iran and sample its 200 stores and shops in the city which has customers randomly selected. The results show that the security apparatus reader has the greatest impact on their satisfaction. In addition the low cost; it is most concerned with customer satisfaction. The remarkable thing is that the devices meet the customer’s card is the least that should be examined. Authorities can resolve individual complaints, the better the card reader devices can capture and customer satisfaction.